A biodegradable paper-plastic composite packaging material and a method for preparing the same

CN122960056APending Publication Date: 2026-10-23ZICAN TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611042884.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

传统的造纸工艺通常大量使用聚酰胺环氧氯丙烷树脂作为湿强剂,但是,聚酰胺环氧氯丙烷树脂中含有二氯丙醇等有毒副产物,且在自然环境中难以降解,不符合当前的环保趋势;因此,造纸行业开始尝试使用双醛淀粉等生物基高分子材料来替代传统的合成树脂湿强剂;现有技术中,例如一些全降解包装纸方案,通常采用表面涂布工艺将双醛淀粉等高分子涂覆于已成型的纸张表面,然而,表面涂布难以实现增强剂在纸张Z向即厚度方向的均匀渗透,易导致层间结合力差,且无法从根本上改善纤维网络内部的交织强度,因此,将双醛淀粉直接引入抄纸湿部进行浆内添加成为提升纸张整体强度的优选途径

Benefits of technology

[0036]本发明在酸性条件下预组装壳聚糖偶联改性木质纤维素纳米纤维与双醛淀粉形成微凝胶悬浮液,并将其加入至pH为7.0-7.5的中性基础木浆中,使壳聚糖链段由质子化状态向去质子化状态转变,促使壳聚糖偶联改性木质纤维素纳米纤维降低溶解度,进而带动包裹在其中的双醛淀粉在木浆纤维表面发生原位微相分离与共沉淀,通过将水溶性的双醛淀粉转化为不溶性的沉淀物并附着于纤维表面,提高了双醛淀粉在浆料体系中的留着率。相比于现有技术中将双醛淀粉用于成纸表面涂布而无法实现内部网络均匀增强的缺陷,或者双醛淀粉直接游离在浆液中易随白水流失的问题,本发明通过湿部浆内添加结合原位微相分离技术,将原本极易流失的水溶性成膜物质转化为可在湿部高效留着的微观沉淀;不仅减少了有效成分的损耗及白水化学需氧量负荷;同时,原位沉淀的包覆结构限制了双醛淀粉在后续干燥脱水过程中的游移,抑制了交联剂在纸页厚度方向上的毛细管迁移,避免了表面富集导致的层间结合力不均。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122960056A_ABST
    Figure CN122960056A_ABST
Patent Text Reader

Abstract

The application discloses a biodegradable paper-plastic composite packaging material and a preparation method thereof, and relates to the technical field of green packaging materials. The chitosan coupling modified lignocellulose nanofiber and dialdehyde starch are pre-prepared into a microgel suspension under the condition that the pH value is 3.5-4.5, and then added into a basic wood pulp suspension with a pH value of 7.0-7.5, so that the deprotonation of the chitosan chain segment occurs and triggers in-situ microphase separation, and the dialdehyde starch is limited in space on the surface of the wood pulp fiber. The wet paper sheet after pressing is treated at a medium temperature of 85-95 DEG C and then solidified at a high temperature of 110-115 DEG C when the moisture content is reduced to 30%-40%, so as to obtain a wood pulp paper base layer. Then, a degradable plastic coating liquid containing polyvinyl alcohol, thermoplastic starch and a plasticizer is coated on at least one side surface of the wood pulp paper base layer, dried and hot-pressed to form a degradable plastic layer, so as to obtain the biodegradable paper-plastic composite packaging material. The application has the wet strength and folding endurance of the wood pulp paper base layer and the surface protection performance of the degradable plastic layer, and is suitable for the field of green packaging materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of green packaging materials technology, and in particular to a biodegradable paper-plastic composite packaging material and its preparation method. Background Technology

[0002] Paper-plastic composite packaging materials typically use paper as the base material to provide stiffness, printability, and structural strength, while a plastic layer improves the material's water resistance, oil resistance, and heat-sealing properties. They are widely used in green packaging and single-use packaging applications. Traditional paper-plastic composite packaging materials often use non-degradable plastics such as polyethylene and polypropylene as the coating or composite layer. After use, the paper and plastic layers are difficult to separate effectively, leading to recycling difficulties and environmental burden. Therefore, replacing traditional non-degradable plastic layers with biodegradable plastic layers, and improving the wet strength, folding endurance, and surface adaptability of the paper base itself, has become an important development direction for green paper-plastic composite packaging materials.

[0003] With the rapid development of the green packaging industry, the wood pulp paper base layer in biodegradable paper-plastic composite packaging materials has placed higher demands on its dry and wet tensile strength, folding endurance, and surface lamination adaptability. Traditional papermaking processes typically use polyamide epichlorohydrin resin as a wet strength agent. However, polyamide epichlorohydrin resin contains toxic byproducts such as dichloropropanol and is difficult to degrade in the natural environment, which is inconsistent with current environmental protection trends. Therefore, the papermaking industry has begun to try using bio-based polymer materials such as dialdehyde starch to replace traditional synthetic resin wet strength agents. In existing technologies, such as some fully biodegradable packaging paper solutions, a surface coating process is usually used to coat the surface of the formed paper with polymers such as dialdehyde starch. However, surface coating makes it difficult to achieve uniform penetration of the reinforcing agent in the Z-direction (thickness direction) of the paper, which easily leads to poor interlayer bonding and cannot fundamentally improve the interweaving strength within the fiber network. Therefore, directly introducing dialdehyde starch into the wet end of papermaking for in-slip addition has become a preferred way to improve the overall strength of the paper.

[0004] However, in actual industrial production, dialdehyde starch has extremely high water solubility, making it difficult to spontaneously adsorb onto negatively charged wood pulp fibers in the wet end of papermaking. This results in extremely low retention, with a large amount of effective components being lost with the white water. This not only increases production costs but also causes serious problems with excessive chemical oxygen demand (COD) in wastewater. To solve the retention problem, existing technologies typically employ the method of directly mixing retention aids such as cationic polyacrylamide or cationic starch into the pulp tank. However, this conventional direct mixing method within the pulp is prone to causing excessive local flocculation in the pulp system, leading to uneven distribution of the aids in the fiber network. This not only has a limited effect on improving the retention rate but also severely damages the uniformity of the paper.

[0005] In addition to imparting wet strength to paper, dialdehyde starch also causes paper embrittlement. The aldehyde groups of dialdehyde starch and the cellulose hydroxyl groups undergo a cross-linking reaction during drying. This cross-linked network solidifies rapidly under conventional high-temperature drying conditions, leading to a loss of relative slippage between fibers. Macroscopically, this manifests as a decrease in the folding endurance of the packaging paper, making it prone to folding and breakage. To address this defect, existing technologies are mostly limited to adjusting the pure chemical formulation, such as adding large amounts of small-molecule plasticizers like glycerol to the system, or lowering the overall operating temperature of the drying cylinder. However, the release of small-molecule plasticizers can damage the paper's water resistance and dry strength; while lowering the overall drying temperature leads to incomplete cross-linking reactions and significantly reduces the paper machine's production efficiency, failing to fundamentally solve the problem.

[0006] In summary, a long-standing technical challenge in this field is the irreconcilable contradiction between high retention rate, high wet strength, and high flexibility in environmentally friendly packaging paper without using traditional toxic synthetic resins. Current technologies lack a systematic process that can effectively decouple this contradiction at the microstructure assembly and drying kinetics levels. Therefore, there is an urgent need to develop a paper-plastic composite packaging material and its preparation method that combines the wet strength, folding endurance, and surface water resistance of a wood pulp paper base layer with the compatibility of a biodegradable plastic layer, in order to overcome the aforementioned industry bottleneck. Summary of the Invention

[0007] This invention overcomes the shortcomings of the prior art and provides a biodegradable paper-plastic composite packaging material and its preparation method. By forming a biodegradable plastic layer on the surface of a wood pulp paper base with wet strength and folding endurance, the resulting material combines the mechanical properties of paper-based materials with the surface protection properties of a biodegradable plastic layer.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing a biodegradable paper-plastic composite packaging material, comprising the following steps:

[0009] S1. Chitosan-coupled modified lignocellulose nanofibers and dialdehyde starch are mixed in water, the pH of the system is adjusted to 3.5-4.5, and the mixture is stirred at 40-50℃ for 30-45 min to obtain a microgel suspension.

[0010] The molar ratio of the aldehyde group in the dialdehyde starch to the amino group in the chitosan-coupled modified lignocellulose nanofiber is 5:1-8:1.

[0011] S2. Adjust the pH value of the basic wood pulp suspension to 7.0-7.5, and then add the alkyl ketene dimer and the microgel suspension obtained in step S1 to the basic wood pulp suspension, and mix them evenly to obtain paper pulp.

[0012] S3. The paper pulp obtained in step S2 is wire-fed, formed, and pressed to obtain a wet paper sheet; the wet paper sheet is subjected to multi-stage drying, wherein when the moisture content of the wet paper sheet drops to 30%-40%, the drying temperature is controlled at 85-95℃ and maintained for 1-2 minutes; then the temperature is raised to 110-115℃ and cured for 30-60 seconds to obtain the wood pulp paper base layer;

[0013] S4. A biodegradable plastic coating liquid containing polyvinyl alcohol, thermoplastic starch and glycerin is coated on at least one side of the wood pulp paper base layer, and then dried and hot-pressed to form a biodegradable plastic layer, thereby obtaining the biodegradable paper-plastic composite packaging material.

[0014] In a preferred embodiment of the present invention, in step S1, the degree of oxidation of the dialdehyde starch is 40%-60%.

[0015] In a preferred embodiment of the present invention, in step S1, the chitosan-coupled modified lignocellulose nanofibers are prepared through the following steps:

[0016] A suspension of lignocellulose nanofibers with carboxyl groups on the surface was mixed with a crosslinking agent for activation treatment. Then, a chitosan solution with a degree of deacetylation ≥95% was added. The mixture was stirred at a constant temperature under conditions of pH 5.0-5.5 and temperature 45-50℃. After the reaction was completed, the nanofibers were washed to obtain the final product.

[0017] The crosslinking agent is a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide.

[0018] In a preferred embodiment of the present invention, in step S2, the basic wood pulp suspension contains calcium carbonate filler;

[0019] The specific steps of adding the alkyl ketene dimer and the microgel suspension prepared in step S1 are as follows:

[0020] First, the alkyl ketene dimer is added to the base wood pulp suspension. Then, the microgel suspension is added dropwise or sprayed into the base wood pulp suspension at a stirring speed of 800-1200 rpm.

[0021] In a preferred embodiment of the present invention, in step S2, the base wood pulp in the base wood pulp suspension is composed of 40-60 parts of long fiber softwood pulp and 40-60 parts of short fiber hardwood pulp, based on the weight parts of oven-dried pulp.

[0022] The long-fiber softwood pulp has a freeness of 38-42°SR, and the short-fiber hardwood pulp has a freeness of 28-32°SR.

[0023] In a preferred embodiment of the present invention, in step S2, after adding the microgel suspension, cationic polyacrylamide is also added to the base wood pulp suspension;

[0024] The amount of cationic polyacrylamide added is 0.02%-0.05% based on the weight of the oven-dry slurry.

[0025] In a preferred embodiment of the present invention, in step S3, the pressing is a multi-stage roller pressing, and the moisture content of the wet paper sheet after being pressed by the multi-stage roller is 50%-55%.

[0026] In a preferred embodiment of the present invention, in step S3, the multi-stage drying is carried out in a multi-cylinder paper machine;

[0027] The drying temperature of 85-95℃ is controlled in the front drying cylinder of the multi-cylinder paper machine, and the temperature is raised to 110-115℃ in the rear drying cylinder of the multi-cylinder paper machine.

[0028] The final moisture content of the cured wood pulp paper base layer is 6%-8%.

[0029] A pulp composition for the wood pulp base layer of a biodegradable paper-plastic composite packaging material includes a base wood pulp suspension, an alkyl ketene dimer, and a microgel suspension.

[0030] The microgel suspension was prepared by mixing chitosan-coupled modified lignocellulose nanofibers with dialdehyde starch in water, adjusting the pH of the system to 3.5-4.5, and stirring the mixture at 40-50℃ for 30-45 minutes.

[0031] The molar ratio of the aldehyde group in the dialdehyde starch to the amino group in the chitosan-coupled modified lignocellulose nanofiber is 5:1-8:1.

[0032] The overall pH value of the slurry composition is 7.0-7.5;

[0033] Based on the weight parts of oven-dried pulp, the base wood pulp in the base wood pulp suspension is 100 parts, the microgel suspension is 3-8 parts by oven-dried mass, and the alkyl ketene dimer is 0.5-1.5 parts.

[0034] A biodegradable paper-plastic composite packaging material is prepared by any of the above-described preparation methods; the biodegradable paper-plastic composite packaging material includes a wood pulp paper base layer and a biodegradable plastic layer disposed on at least one side surface of the wood pulp paper base layer.

[0035] This invention addresses the shortcomings of the prior art and has the following beneficial effects:

[0036] This invention pre-assembles chitosan-coupled modified lignocellulose nanofibers and dialdehyde starch into a microgel suspension under acidic conditions, and adds it to neutral basic wood pulp with a pH of 7.0-7.5. This causes the chitosan segments to transition from a protonated state to a deprotonated state, reducing the solubility of the chitosan-coupled modified lignocellulose nanofibers. Consequently, the dialdehyde starch encapsulated within the nanofibers undergoes in-situ microphase separation and co-precipitation on the surface of the wood pulp fibers. By converting the water-soluble dialdehyde starch into an insoluble precipitate that adheres to the fiber surface, the retention rate of dialdehyde starch in the pulp system is improved. Compared to existing technologies that use dialdehyde starch for paper surface coating but fail to achieve uniform reinforcement of the internal network, or where dialdehyde starch is directly free in the pulp and easily lost with white water, this invention, through wet-end pulp addition combined with in-situ microphase separation technology, transforms the originally easily lost water-soluble film-forming substance into a micro-precipitate that can be efficiently retained in the wet end. This not only reduces the loss of effective components and the chemical oxygen demand load of white water, but also, the coating structure of the in-situ precipitate restricts the migration of dialdehyde starch during subsequent drying and dehydration processes, inhibits the capillary migration of crosslinking agents in the thickness direction of the paper sheet, and avoids uneven interlayer bonding caused by surface enrichment.

[0037] This invention involves maintaining the paper's moisture content at 85-95℃ for 1-2 minutes when it drops to 30%-40%, followed by curing at 110-115℃. Under these moderate temperatures (85-95℃) and in the presence of moisture, the lignin segments precipitated on the fiber surface expand, providing stress relaxation time for the physical shrinkage of the fiber network. The subsequent high temperature of 110-115℃ causes the free aldehyde groups to undergo a hemiacetal reaction with the cellulose hydroxyl groups, forming cross-links. This achieves a phased separation between the physical arrangement of the fiber network and the chemical cross-linking reaction, constructing a semi-interpenetrating network containing flexible lignin segments at the fiber interlacing nodes. Compared to the problems of excessively rapid cross-linking reactions and stress concentration within the fiber micro-interfaces caused by the one-step high-temperature drying method in existing technologies, this invention reduces residual stress within the paper, improving its flexibility and folding endurance while maintaining its wet tensile strength.

[0038] This invention combines a pH-triggered in-situ precipitation process with a gradient drying process at a specific moisture content. The core-shell structure formed by the in-situ precipitation fixes the dialdehyde starch, providing a stable reaction site for gradient drying. Meanwhile, the temperature curve of the gradient drying matches the thermodynamic transformation characteristics of the precipitated complex. This combination simultaneously improves the uniformity of crosslinking agent distribution and the flexibility of the crosslinking network. Compared to traditional papermaking processes using synthetic resins such as polyamide and epichlorohydrin, this invention primarily uses starch, chitosan, and cellulose components to construct the reinforcing network in the wood pulp paper base layer, reducing the use of traditional wet-strength resins and avoiding the introduction of toxic byproducts such as dichloropropanol. Simultaneously, by forming a biodegradable plastic layer on the surface of the wood pulp paper base layer, the resulting paper-plastic composite packaging material is more adaptable to the environmentally friendly treatment requirements of green packaging materials.

[0039] This invention introduces calcium carbonate filler into basic wood pulp and adds the microgel suspension dropwise or by spraying at a stirring speed of 800-1200 rpm. The acid-base buffering capacity of calcium carbonate, combined with its high shear dispersion effect, ensures that when acidic microgels enter the neutral pulp tank, the local acid-base neutralization reaction is rapidly dispersed, maintaining the overall pH stability of the pulp tank and avoiding the disruption of the neutral sizing environment of alkyl ketene dimers caused by excessively low local pH values. More importantly, this invention utilizes the synergistic effect of specific feeding sequence and phase change precipitation: the alkyl ketene dimer particles pre-dispersed in the pulp, at the moment of deprotonation and in-situ precipitation of the microgels, generate a strong physical entrapment and co-precipitation effect through the three-dimensional floc network formed by the precipitation. Compared to the conventional method of directly pouring acidic additives, which easily leads to excessive local flocculation of pulp, hydrolysis of sizing agents, and low retention of sizing agents, this invention not only solves the retention problem of dialdehyde starch, but also utilizes this phase change process to significantly improve the retention rate and distribution of alkyl ketene dimers on the fiber surface, achieving synergistic retention of reinforcing agents and sizing agents, enhancing the surface water-resistant properties of wood pulp paper base layers, and ensuring the stability of continuous papermaking processes.

[0040] This invention further involves forming a biodegradable plastic layer composed of polyvinyl alcohol, thermoplastic starch, and a plasticizer on at least one side of the wood pulp paper base layer, transforming the resulting material from a single wood pulp paper base layer into a paper-plastic composite packaging material. The biodegradable plastic layer can form a continuous film on the surface of the wood pulp paper base layer, improving the material's surface coverage, flexibility, and packaging adaptability. Simultaneously, the resulting paper-plastic composite packaging material maintains a high final aerobic biodegradability, making it more suitable for green packaging and subsequent environmentally friendly processing. Attached Figure Description

[0041] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0042] Figure 1 This is a flowchart of a method for preparing a biodegradable paper-plastic composite packaging material according to the present invention. Detailed Implementation

[0043] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0044] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein. Therefore, the scope of protection of the invention is not limited to the specific embodiments disclosed below.

[0045] The embodiments and comparative examples of the present invention pertain to a biodegradable paper-plastic composite packaging material and its preparation method; wherein, S1 to S3 in the embodiments and comparative examples are mainly used to prepare a wood pulp paper base layer, and S4 is used to form a biodegradable plastic layer on the surface of the wood pulp paper base layer. The resulting material is suitable for green packaging scenarios that require wet tensile strength, folding endurance and environmental treatment adaptability.

[0046] Experimental materials and reagents:

[0047] Chitosan: Product No. C105799, degree of deacetylation ≥95%, viscosity 100-200 mPa.s, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0048] Dialdehyde starch: Analytical grade reagent with an oxidation degree of 50%, catalog number T81890, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0049] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride: Analytical grade reagent with a purity ≥98.0%, catalog number E106172, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0050] N-Hydroxysuccinimide: Analytical grade reagent with a purity ≥98.0%, catalog number S20179, was purchased from Shanghai Yuanye Biotechnology Co., Ltd.

[0051] 2,2,6,6-Tetramethylpiperidine-1-oxide: Analytical grade reagent with a purity of 98%, catalog number 214000, purchased from Sigma-Aldrich.

[0052] Sodium bromide: Analytical grade reagent with a purity ≥99.0%, catalog number 310506, purchased from Sigma-Aldrich.

[0053] Sodium hypochlorite solution: Analytical grade reagent with an available chlorine content of 10% to 15%, catalog number 425044, purchased from Sigma-Aldrich.

[0054] Long fiber softwood pulp: Commercially available Canadian bleached sulfate softwood pulp.

[0055] Short fiber hardwood pulp: Commercially available conventional bleached sulfate hardwood pulp is used.

[0056] Unbleached sulfate softwood pulp: Commercially available unbleached softwood pulp containing residual lignin is used.

[0057] Alkyl ketene dimer: Made from commercially available conventional paper industry-grade neutral sizing agent emulsion with an effective solid content of 15%.

[0058] Cationic polyacrylamide: Commercially available conventional paper industry-grade retention aid with a molecular weight of 8 million to 10 million and an ionicity of 30%.

[0059] Calcium carbonate: Commercially available conventional paper-grade heavy calcium carbonate filler with an average particle size of 2.0 μm is used.

[0060] Hydrochloric acid: Prepared into a 0.1 mol / L dilute solution using commercially available analytical grade reagents.

[0061] Sodium hydroxide: Prepared into a 0.1 mol / L dilute solution using commercially available analytical grade reagents.

[0062] Glacial acetic acid: Prepared into a 1% aqueous solution of acetic acid using commercially available analytical grade reagents.

[0063] Polyvinyl alcohol: Commercially available polyvinyl alcohol is used, with a degree of alcoholysis of 87%-89%, and a viscosity of 20-26 mPa·s for a 4wt% aqueous solution at 20℃.

[0064] Thermoplastic starch: Commercially available corn starch-based thermoplastic starch powder with a starch content ≥75% and moisture content ≤5%.

[0065] Glycerin: Commercially available analytical grade glycerin was used as a plasticizer for the biodegradable plastic layer.

[0066] Homemade materials:

[0067] This preparation example provides a method for synthesizing chitosan-coupled modified lignocellulose nanofibers, specifically including the following steps:

[0068] 100g of oven-dry weight of unbleached sulfate softwood pulp was dispersed in water to prepare a pulp suspension with a mass concentration of 1%. 1.6g of 2,2,6,6-tetramethylpiperidine-1-oxide and 10g of sodium bromide were added to the pulp suspension in sequence and stirred until homogeneous.

[0069] At room temperature, sodium hypochlorite solution was slowly added dropwise at a ratio of 5 mmol sodium hypochlorite per gram of oven-dry slurry. During the addition of sodium hypochlorite solution, the pH value of the system was maintained between 10.0 and 10.5 by supplementing with 0.5 mol / L sodium hydroxide solution.

[0070] Stop adding sodium hypochlorite solution when the pH value stops decreasing. Centrifuge and wash the reaction solution until it is neutral. Then, use a high-pressure homogenizer to cycle it 5 times at an operating pressure of 80 MPa to mechanically dissociate it and obtain a lignocellulose nanofiber suspension with carboxyl groups on the surface.

[0071] Weigh 5g of chitosan with a degree of deacetylation ≥95% and slowly add it to 500mL of 1% acetic acid aqueous solution. Stir magnetically at room temperature until fully dissolved to obtain a homogeneous chitosan solution.

[0072] Take 1000 mL of 1% lignocellulose nanofiber suspension and adjust the pH to 5.0. Add 2.0 g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and 1.2 g of N-hydroxysuccinimide to the lignocellulose nanofiber suspension. Stir and activate at room temperature in the dark for 2 hours to convert the carboxyl groups on the surface of the lignocellulose nanofibers into active esters.

[0073] Chitosan solution was slowly added dropwise to the activated lignocellulose nanofiber suspension, the pH of the system was adjusted to 5.0 to 5.5 and the temperature was raised to 45°C. The amidation coupling reaction was carried out by stirring at a constant temperature for 12 hours.

[0074] The reaction products were placed in dialysis bags with a molecular weight cutoff of 8000 Da to 14000 Da and dialyzed in distilled water for 72 hours to remove unreacted crosslinking agents and small molecule impurities.

[0075] The dialyzed suspension was then centrifuged at 10,000-15,000 rpm for 15-20 minutes. The supernatant containing free unreacted chitosan was discarded, and the lower precipitate was redispersed in deionized water. The centrifugation and washing were repeated three times to finally obtain a pure chitosan-coupled modified lignocellulose nanofiber suspension with positively charged amino groups.

[0076] After centrifugation and washing, samples were taken and freeze-dried. The amino content (mmol / g oven-dry) of the chitosan-coupled modified lignocellulose nanofibers was determined by conductivity titration to provide a basis for subsequent calculations based on precise molar ratios. In this preparation example, the amino content was measured to be 0.45 mmol / g oven-dry.

[0077] like Figure 1 As shown, a method for preparing a biodegradable paper-plastic composite packaging material includes the following steps:

[0078] S1. Chitosan-coupled modified lignocellulose nanofibers and dialdehyde starch are mixed in water, the pH of the system is adjusted to 3.5-4.5, and the mixture is stirred at 40-50℃ for 30-45 min to obtain a microgel suspension.

[0079] The molar ratio of the aldehyde group in the dialdehyde starch to the amino group in the chitosan-coupled modified lignocellulose nanofiber is 5:1-8:1.

[0080] S2. Adjust the pH value of the basic wood pulp suspension to 7.0-7.5, and then add the alkyl ketene dimer and the microgel suspension obtained in step S1 to the basic wood pulp suspension, and mix them evenly to obtain paper pulp.

[0081] S3. The paper pulp obtained in step S2 is wire-fed, formed, and pressed to obtain a wet paper sheet; the wet paper sheet is subjected to multi-stage drying, wherein when the moisture content of the wet paper sheet drops to 30%-40%, the drying temperature is controlled at 85-95℃ and maintained for 1-2 minutes; then the temperature is raised to 110-115℃ and cured for 30-60 seconds to obtain the wood pulp paper base layer;

[0082] S4. A biodegradable plastic coating liquid containing polyvinyl alcohol, thermoplastic starch and glycerin is coated on at least one side surface of the wood pulp paper base layer, wherein the mass ratio of polyvinyl alcohol, thermoplastic starch and glycerin is 10:5:2 and the solid content of the biodegradable plastic coating liquid is 17wt%. The biodegradable plastic layer is formed by drying and hot pressing to obtain the biodegradable paper-plastic composite packaging material.

[0083] The core concept of this invention lies in first utilizing the metastable pre-assembly of chitosan-coupled modified lignocellulose nanofibers and dialdehyde starch under acidic conditions, combined with in-situ microphase separation triggered by a neutral papermaking environment, to spatially confine the dialdehyde starch to the surface of the wood pulp fibers, thereby obtaining a wood pulp paper base layer with wet strength and folding endurance. Subsequently, a biodegradable plastic layer is formed on at least one side of the surface of the wood pulp paper base layer, transforming the resulting material from a single wood pulp packaging paper into a paper-plastic composite packaging material. This approach retains the internal reinforcing network of the wood pulp paper base layer while utilizing the biodegradable plastic layer to improve the surface protective adaptability of the material.

[0084] Specifically, in step S1, the pH of the system is adjusted to 3.5 to 4.5 so that the amino groups on the surface of the chitosan-coupled modified lignocellulose nanofibers are in a protonated state and carry a positive charge. The system is maintained in a metastable state by using electrostatic repulsion, thus preventing premature flocculation and precipitation of the dialdehyde starch and the chitosan-coupled modified lignocellulose nanofibers.

[0085] Furthermore, in step S1, the molar ratio of aldehyde groups in the dialdehyde starch to amino groups in the chitosan-coupled modified lignocellulose nanofibers is controlled to be 5:1 to 8:1, so that the aldehyde groups are in an excess state. The excess free aldehyde groups are physically encapsulated inside the three-dimensional microgel network composed of chitosan-coupled modified lignocellulose nanofibers, thus reserving reactive groups for subsequent cross-linking reactions.

[0086] Preferably, in step S1, the temperature is controlled at 40°C to 50°C and the reaction is stirred for 30 to 45 minutes, which provides the activation energy and kinetic time required for microgel pre-assembly, ensuring that the dialdehyde starch is uniformly coated; if the temperature is too high or the time is too long, starch will degrade, and if the temperature is too low or the time is too short, a stable microgel suspension cannot be formed.

[0087] Furthermore, after obtaining the microgel suspension in step S1, since the microgel contains unreacted active aldehyde and amino groups and is a heat-sensitive system, it is preferable to use freeze-drying or vacuum low-temperature drying to sample and determine the accurate solid content of the microgel suspension; and based on the determination results, the mass concentration of the microgel suspension is calibrated to a standard concentration by adding deionized water or centrifugation concentration, so as to provide a benchmark for accurate measurement in step S2.

[0088] Specifically, in step S2, the pH value of the basic wood pulp suspension is adjusted to 7.0 to 7.5. When the acidic microgel suspension enters the neutral basic wood pulp suspension, the increase in the ambient pH value causes the chitosan segments to change from a protonated state to a deprotonated state. The increase in the ambient pH value triggers the deprotonation of chitosan-coupled modified lignocellulose nanofibers and reduces their solubility, forcing the dialdehyde starch encapsulated therein to undergo in-situ microphase separation and co-precipitation on the surface of the wood pulp fibers, thus cutting off the capillary migration path of the dialdehyde starch in the subsequent dehydration process.

[0089] Meanwhile, since alkyl ketene dimers were added to the system before the microgel suspension was added, the free alkyl ketene dimer particles were in situ encapsulated and trapped on the surface of the wood pulp fibers during the instantaneous phase change precipitation of the microgel. This process combines the originally separate sizing agent retention process and reinforcing agent precipitation process into one, and the phase change trapping effect of the microgel significantly improves the retention rate of alkyl ketene dimers, avoiding the loss of sizing agent with white water.

[0090] Preferably, the base wood pulp suspension contains calcium carbonate filler, and the microgel suspension is added dropwise or sprayed at a stirring speed of 800 rpm to 1200 rpm.

[0091] The acid-base buffering capacity of calcium carbonate filler, combined with its high shear dispersion effect, can neutralize and disperse the local acidity brought about by the acidic microgel suspension, maintain the overall pH stability of the base wood pulp suspension, and prevent the local pH value from being too low, thus disrupting the neutral sizing environment of the alkyl ketene dimer. In addition, the high shear force ensures that the microgel can be fully mixed with the alkyl ketene dimer before the phase change precipitation occurs, thereby maximizing the coprecipitation and trapping efficiency.

[0092] Specifically, in step S3, when the moisture content of the wet paper sheet drops to 30% to 40%, the drying temperature is controlled at 85°C to 95°C and maintained for 1 to 2 minutes;

[0093] In continuous multi-cylinder papermaking machine production, the maintenance of 1 to 2 minutes is achieved by matching the running speed of the papermaking machine with the total length of the wrap angle of the paper web in the front drying cylinder group. At the same time, the relative humidity in the dehumidification hood of the front drying cylinder group is adjusted to suppress the excessive evaporation of moisture, thereby ensuring that the moisture content of the paper sheet is still maintained in the range of 30% to 40% when it leaves the front drying cylinder group.

[0094] The temperature range of 85℃ to 95℃ matches the glass transition temperature of the flexible lignin segments in the precipitation complex. Under the plasticizing effect of 30% to 40% moisture, the flexible lignin segments expand, providing stress relaxation time for the physical shrinkage of the wood pulp fiber network and avoiding premature rigid locking of cross-links.

[0095] Further, in step S3, the temperature is raised to 110°C to 115°C and cured for 30 to 60 seconds; the high temperature of 110°C to 115°C causes the free aldehyde groups to react with the hydroxyl groups of the wood pulp fibers in a hemiacetal reaction, which is cured at the fiber interlacing nodes after stress relaxation to form a cross-linked network, giving the wood pulp paper base layer the required wet tensile strength.

[0096] Further, in step S4, polyvinyl alcohol is dissolved in water by heating, followed by the addition of thermoplastic starch and glycerol as a plasticizer, and mixed to prepare a biodegradable plastic coating solution. This biodegradable plastic coating solution is then coated onto at least one surface of a wood pulp paper substrate, and after drying and hot pressing, a biodegradable plastic layer is formed. Polyvinyl alcohol is used to form a continuous film layer, thermoplastic starch is used to increase the content of biodegradable materials in the film layer, and glycerol is used to improve the flexibility and film-forming adaptability of the film layer. The biodegradable plastic layer improves the surface protection adaptability of the resulting paper-plastic composite packaging material, making it more suitable for green packaging scenarios.

[0097] Example 1:

[0098] This embodiment provides a method for preparing a biodegradable paper-plastic composite packaging material, which specifically includes the following steps.

[0099] S1. Add 7.5g of dialdehyde starch with an oxidation degree of 50% to 142.5g of deionized water, heat and stir at 92℃ for 1.5 hours to fully gelatinize and dissolve it, and cool to room temperature to obtain a dialdehyde starch solution with a mass concentration of 5wt%.

[0100] Weigh 1000g of a 1.5wt% chitosan-coupled modified lignocellulose nanofiber suspension. Based on the previously determined amino content, add 150g of a 5.0wt% dialdehyde starch solution, followed by 580g of deionized water, to make the total mass of the system 1730g. The initial total solid content of the system is 1.3wt%. Mix thoroughly. At this point, the molar ratio of aldehyde groups in the dialdehyde starch to amino groups in the chitosan-coupled modified lignocellulose nanofiber is 6.9:1, which means the oven-dry mass ratio of dialdehyde starch to chitosan-coupled modified lignocellulose nanofiber is 1:2.

[0101] The pH of the system was adjusted to 4.0 using 0.1 mol / L hydrochloric acid, and the mixture was stirred continuously at 300 rpm for 40 minutes at 45°C to obtain a microgel suspension. Subsequently, 30 g of the microgel suspension sample was accurately measured, and its solid content was determined to be 1.3 wt% using the freeze-drying method. Based on the measurement results, 510 g of deionized water was added to the remaining 1700 g of microgel suspension (containing 22.1 g of oven-dried solids), and its solid content (mass fraction) was accurately determined to be 1.0 wt%.

[0102] S2. Mix 50g of oven-dry weight long-fiber softwood pulp with a freeness of 40°SR and 50g of oven-dry weight short-fiber hardwood pulp with a freeness of 30°SR, add 9900g of pure water to prepare a base wood pulp suspension with a mass concentration of 1.0%, add 10g of calcium carbonate filler to the base wood pulp suspension, and adjust the pH value of the base wood pulp suspension to 7.2 using 0.1mol / L sodium hydroxide solution.

[0103] At a stirring speed of 1000 rpm, 1.0 g of alkyl ketene dimer emulsion, which is equivalent to 6.67 g of commercially available emulsion with an effective solid content of 15%, was added to the base wood pulp suspension. The prepared microgel suspension with a calibrated concentration was added dropwise to the base wood pulp suspension. 500 g of the microgel suspension with a mass concentration of 1.0 wt% was accurately weighed to control the effective solid content of the microgel suspension to be 5.0 g.

[0104] After the addition is complete, 0.03 g of cationic polyacrylamide by oven dry weight is added to the basic wood pulp suspension and mixed evenly to obtain the paper pulp.

[0105] S3. The pulp is wired and formed into a paper sheet, and the moisture content of the wet paper sheet is reduced to 52% through multi-stage pressing;

[0106] The pressed wet paper sheet is dried in multiple stages. First, the wet paper sheet is introduced into the pre-drying cylinder group with the temperature controlled at 65℃ for low-temperature pre-drying to avoid premature cross-linking reaction of dialdehyde starch.

[0107] When the moisture content of the wet paper sheet drops to 35%, transfer the wet paper sheet to a constant temperature and humidity chamber with temperature and humidity control, or cover the upper and lower surfaces of the wet paper sheet with a high-temperature resistant polytetrafluoroethylene breathable membrane to limit moisture evaporation, control the drying temperature to 90℃ and maintain it for 1.5 minutes, and ensure that the moisture content of the paper sheet is not less than 30% at the end of this stage;

[0108] The restrictions were then removed, and the paper was heated to 112°C for 45 seconds to cure. When the final moisture content of the paper dropped to 7%, it was calendered and wound to obtain the wood pulp paper base layer.

[0109] S4. Add 10g of polyvinyl alcohol to 83g of deionized water and stir at 300rpm for 60min at 90℃ to fully dissolve the polyvinyl alcohol. Then, lower the system temperature to 75℃, add 5g of thermoplastic starch and 2g of glycerol, and continue stirring for 30min to obtain a biodegradable plastic coating liquid with a solid content of 17wt%.

[0110] Using a bar coating method, the biodegradable plastic coating liquid is uniformly coated on one side surface of the wood pulp paper base layer obtained in step S3, and the wet film thickness is controlled to be 100 μm. Then, it is dried at 80°C for 5 min. The dried composite material is hot-pressed at 100°C and 0.2 MPa for 30 s to form a biodegradable plastic layer with a dry coating weight of about 17 g / m² and a thickness of 15 ± 2 μm, thus obtaining a biodegradable paper-plastic composite packaging material.

[0111] Example 2:

[0112] The only difference between this embodiment and Embodiment 1 is that in step S1, the pH value of the system is adjusted to 3.5, while the other steps and parameters are consistent with those in Embodiment 1.

[0113] Example 3:

[0114] The only difference between this embodiment and Embodiment 1 is that in step S1, the pH value of the system is adjusted to 4.5, while the other steps and parameters are consistent with those in Embodiment 1.

[0115] Example 4:

[0116] The only difference between this embodiment and Embodiment 1 is that in step S3, the drying temperature is controlled at 85°C, while the other steps and parameters are consistent with those in Embodiment 1.

[0117] Example 5:

[0118] The only difference between this embodiment and Embodiment 1 is that in step S3, the drying temperature is controlled at 95°C, while the other steps and parameters are consistent with those in Embodiment 1.

[0119] Example 6:

[0120] The only difference between this embodiment and Example 1 is that the effective component of the alkyl ketene dimer emulsion added in step S2 is 0.5g; the remaining steps and parameters are consistent with those of Example 1.

[0121] Example 7:

[0122] The only difference between this embodiment and Example 1 is that the effective component of the alkyl ketene dimer emulsion added in step S2 is 1.5g; the remaining steps and parameters are consistent with those of Example 1.

[0123] Comparative Example 1:

[0124] The only difference between this comparative example and Example 1 is that in step S1, the pH value of the system is adjusted to 3.0, while the other steps and parameters are the same as in Example 1.

[0125] Comparative Example 2:

[0126] The only difference between this comparative example and Example 1 is that in step S1, the pH value of the system is adjusted to 6.0, while the other steps and parameters are the same as in Example 1.

[0127] Comparative Example 3:

[0128] The only difference between this comparative example and Example 1 is that in step S3, the drying temperature is controlled at 75°C, while the other steps and parameters are consistent with those of Example 1.

[0129] Comparative Example 4:

[0130] The only difference between this comparative example and Example 1 is that in step S3, the drying temperature is controlled at 105°C, while the other steps and parameters are consistent with those of Example 1.

[0131] Comparative Example 5:

[0132] The only difference between this comparative example and Example 1 is that step S1 is omitted;

[0133] In step S2, the basic wood pulp suspension with pH adjusted to 7.2 is placed under a stirring speed of 1000 rpm, and 1.0 g of alkyl ketene dimer, chitosan-coupled modified lignocellulose nanofiber suspension containing an equal amount of amino groups, dialdehyde starch containing an equal amount of aldehyde groups, and 0.03 g of cationic polyacrylamide are added directly in sequence and mixed evenly to obtain paper pulp.

[0134] In step S3, the pressed wet paper sheet is directly cured and dried at 112°C until the final moisture content is 7%, without undergoing a medium-temperature holding treatment at 90°C. The remaining steps and parameters are consistent with those in Example 1.

[0135] Comparative Example 6:

[0136] The only difference between this comparative example and Example 1 is that the order of adding the alkyl ketene dimer and the microgel suspension in step S2 is reversed.

[0137] Specifically, the microgel suspension of a calibrated concentration was first added dropwise to a basic wood pulp suspension with a pH of 7.2 at a stirring speed of 1000 rpm. After the microgel underwent a phase change and precipitation, 1.0 g of the active ingredient, alkyl ketene dimer emulsion, was added to the system. The remaining steps and parameters were consistent with those in Example 1.

[0138] Comparative Example 7:

[0139] The only difference between this comparative example and Example 1 is that the effective component of the alkyl ketene dimer emulsion added in step S2 is 0.2g; the remaining steps and parameters are consistent with those of Example 1.

[0140] Comparative Example 8:

[0141] The only difference between this comparative example and Example 1 is that the effective component of the alkyl ketene dimer emulsion added in step S2 is 2.0 g; the remaining steps and parameters are consistent with those of Example 1.

[0142] In the following performance tests, the test objects for the dialdehyde starch retention rate, wet tensile strength retention rate, folding endurance, Z-direction aldehyde signal variance, and surface water absorption are the wood pulp paper base layer obtained in steps S1 to S3; the test object for biodegradability performance is the biodegradable paper-plastic composite packaging material obtained after completing step S4.

[0143] The performance of the wood pulp paper base layer, the pulp used in the production process, and the paper-plastic composite packaging material obtained after completing step S4 were tested in Examples 1 to 7 and Comparative Examples 1 to 8. The specific test indicators and test methods are as follows:

[0144] Wet tensile strength retention rate test:

[0145] The dry tensile strength of paper was determined by the constant-rate tensile method specified in the current national standard GB / T 12914-2018. The wet tensile strength was determined by immersing the paper sample in deionized water for 1 hour according to the method specified in the current national standard GB / T 465.2-2008. The percentage of wet tensile strength to dry tensile strength was calculated and recorded as the wet tensile strength retention rate.

[0146] Flexural endurance test:

[0147] According to the method specified in the current national standard GB / T 457-2008 "Determination of folding endurance of paper and paperboard", the number of folds that a paper sample can withstand is determined using an MIT folding endurance tester under standard temperature and humidity conditions, and the result is recorded as folding endurance.

[0148] Dialdehyde starch retention rate test:

[0149] The filtrate collected during the paper pulp web forming process was used as a white water sample. The concentration of unreacted free dialdehyde starch in the white water sample was determined by hydroxylamine hydrochloride titration. Based on the difference between the initial total mass of dialdehyde starch added to the pulp system and the total mass of dialdehyde starch lost in the white water, the percentage of the mass of dialdehyde starch retained on the wood pulp fibers was calculated as the dialdehyde starch retention rate.

[0150] Z-axis aldehyde signal variance test:

[0151] A cross-sectional sample of the wood pulp paper substrate was taken, and a confocal Raman microscope was used to perform a linear scan along the thickness direction (Z-axis) of the paper substrate. Ten test points were selected at equal intervals between the top and bottom surfaces of the cross-section, and the position of each test point at 1730 cm was recorded. -1 The wavenumber corresponds to the Raman characteristic peak intensity of the stretching vibration of the aldehyde carbon-oxygen double bond, and the intensity of each test point at 1095 cm⁻¹ is recorded. -1 The Raman characteristic peak intensity corresponding to the vibration of the cellulose COC skeleton at the wavenumber was used as an internal standard reference; each test point was set at 1730 cm⁻¹. -1The peak intensity at 1095 cm⁻¹ divided by its value at 1095 cm⁻¹ -1 The peak intensity at the test point is used to obtain the relative peak intensity ratio of that test point; the statistical variance of these 10 relative peak intensity ratio data is calculated and denoted as the Z-direction aldehyde signal variance. The smaller the value of the Z-direction aldehyde signal variance, the more uniform the distribution of dialdehyde starch in the thickness direction of the paper.

[0152] Surface water absorption (Cobb value) test:

[0153] According to the current national standard GB / T 1540-2002 "Determination of water absorption of paper and paperboard (Cobb method)", the Cobb 60 value (g / m²) of the front side of the paper is determined. 2 The lower the Cobb value, the better the surface water resistance of the paper, which indirectly reflects the retention rate and sizing effect of alkyl ketene dimers in the paper network.

[0154] Biodegradability performance test:

[0155] According to the method specified in GB / T 19277.1-2025 "Determination of final aerobic biodegradability of materials under controlled composting conditions—Method for determining the amount of carbon dioxide released—Part 1: General Method", the final aerobic biodegradability of paper-plastic composite packaging materials prepared after completing step S4 in Examples 1 to 7 and Comparative Examples 1 to 8 was tested for 180 days. The biodegradability rate of the paper-plastic composite packaging materials was calculated based on the amount of carbon dioxide released by the samples during the test. Three parallel samples were set up in each group, and the average value of the test results was recorded as the 180-day biodegradability rate.

[0156] The test results are summarized in Table 1:

[0157] Table 1 Summary of Performance Test Data for Examples and Comparative Examples

[0158] Group Dialdehyde starch retention rate / % Wet tensile strength retention rate / % Flexural endurance / time Z-directed aldehyde signal variance <![CDATA[Cobb 60 value (g / m 2 )]]> 180d biodegradation rate / % Example 1 95.2 38.5 165 0.12 22.5 91.8 Example 2 91.4 36.2 152 0.18 24.1 92.0 Example 3 92.7 37.1 158 0.15 23.6 91.7 Example 4 94.8 35.4 168 0.13 22.8 92.3 Example 5 95 39.1 145 0.14 22.6 91.2 Example 6 95.5 38.8 168 0.11 27.2 92.6 Example 7 94.8 36.5 155 0.13 19.5 90.9 Comparative Example 1 65.3 22.4 85 0.85 35.2 92.7 Comparative Example 2 72.1 25.6 92 0.64 31.8 92.4 Comparative Example 3 94.5 31.2 76 0.15 24.5 93.0 Comparative Example 4 95.1 38.8 62 0.14 23.2 90.6 Comparative Example 5 45.6 28.5 45 1.85 48.6 92.8 Comparative Example 6 94.6 37.8 161 0.14 39.4 91.7 Comparative Example 7 95.6 39.0 170 0.11 46.5 93.4 Comparative Example 8 93.5 26.4 105 0.16 18.2 89.8

[0159] Note: The test objects for the dialdehyde starch retention rate, wet tensile strength retention rate, folding endurance, Z-direction aldehyde signal variance and Cobb60 value are the wood pulp paper base layer obtained in steps S1 to S3; the test object for the 180d biodegradability rate is the paper-plastic composite packaging material obtained after completing step S4.

[0160] Comparing the test data of Example 1 and Comparative Example 5, it can be seen that the retention rate of dialdehyde starch in Example 1 reached 95.2% and the variance of Z-axis aldehyde group signal was only 0.12, while the retention rate of dialdehyde starch in Comparative Example 5 was only 45.6% and the variance of Z-axis aldehyde group signal was as high as 1.85. It should be noted that Comparative Example 5 did not use microgel pre-preparation and did not undergo medium-temperature holding treatment. It represents the conventional manufacturing process of "direct mixing in pulp + one-step high-temperature drying" in the prior art. The performance of Comparative Example 5 was the worst in all aspects, which fully demonstrates that under the traditional process, dialdehyde starch is easily lost with white water and is unevenly distributed. At the same time, the internal stress of the fibers cannot be released, resulting in brittle paper.

[0161] Furthermore, due to the lack of a trapping effect from microgel phase change precipitation, the alkyl ketene dimer in Comparative Example 5 is also easily lost with water, resulting in poor surface water resistance of the wood pulp paper base layer. Example 1, through the combination of acidic pre-preparation of microgel suspension and neutral pulping environment, as well as gradient drying at a specific moisture content, overcomes the traditional process defects of Comparative Example 5. It not only achieves efficient retention of dialdehyde starch, but also synergistically improves the retention effect of sizing agent, proving that there is a significant synergistic effect between the steps of the present invention. It promotes the deprotonation of chitosan segments and triggers in-situ microphase separation, confining the dialdehyde starch to the surface of wood pulp fibers, overcoming the defect of dialdehyde starch being directly free in the pulp and easily lost with white water in Comparative Example 5. The in-situ precipitation coating structure blocks the capillary migration path of dialdehyde starch in the subsequent dewatering process, avoids the enrichment of crosslinking agent on the paper surface, and ensures the uniformity of the crosslinking network in the thickness direction of the paper.

[0162] Comparing the test data of Example 1 with those of Comparative Examples 1 and 2, it can be seen that when the pH value of the microgel pre-preparation is reduced to 3.0 or increased to 6.0, the retention rate of dialdehyde starch decreases to 65.3% and 72.1%, respectively, and the variance of the Z-direction aldehyde group signal increases to 0.85 and 0.64, respectively. The strong acid environment with a pH value of 3.0 induces an electrostatic shielding effect and leads to the degradation of polymer chains, destroying the metastable encapsulation structure of the microgel. The environment with a pH value of 6.0 fails to effectively form the expected protonation / deprotonation transition difference, causing the microgel to flocculate prematurely in the pre-preparation stage and unable to form a uniform in-situ precipitation in the slurry preparation stage. The pH value range of 3.5 to 4.5 is a necessary physicochemical condition for maintaining metastable state and achieving subsequent phase transition confinement.

[0163] Comparing the test data of Example 1 with those of Comparative Example 3 and Comparative Example 4, it can be seen that, under the premise that the variance of the Z-axis aldehyde group signal remains at a low level, the folding endurance of Example 1 reaches 165 times, while the folding endurance of Comparative Example 3 and Comparative Example 4 decreases to 76 times and 62 times, respectively. In Comparative Example 3, the drying temperature of 75°C failed to reach the glass transition temperature of the lignin flexible chain segment in the precipitated complex. The lignin flexible chain segment could not effectively stretch under the plasticization of moisture, resulting in the inability to release the internal stress of fiber shrinkage. For Comparative Example 4, although the high-temperature drying of 105°C made the hemiacetal crosslinking reaction rapid and thorough (therefore, its wet tensile strength retention rate reached a relatively high level of 38.8%), it was precisely because of the lack of the medium-temperature stress relaxation stage of 85-95°C that the kinetic rate of the crosslinking network exceeded the physical stress relaxation rate, and the crosslinking network was prematurely rigidly locked. This stress concentration within the microscopic interface severely damages the paper's flexibility, manifesting macroscopically as paper embrittlement and a significant decrease in folding endurance. This proves that the medium-temperature treatment of 85°C to 95°C combined with specific moisture content conditions in this invention achieves a phased separation of the physical arrangement of the fiber network and the chemical cross-linking reaction, which is a necessary technical means to maintain a key balance between paper strength and improved flexibility.

[0164] Furthermore, comparing the test data of Examples 1, 6, and 7 with those of Comparative Examples 7 and 8 reveals that the amount of alkyl ketene dimer added has a significant critical impact on the overall performance of the paper. When the amount of alkyl ketene dimer added is too low, such as 0.2 g in Comparative Example 7, even with the microgel trapping effect, a continuous hydrophobic film cannot be formed on the fiber surface, resulting in a Cobb value as high as 46.5 g / m². 2 This fails to meet the water-blocking requirements of wood pulp paper substrates; conversely, when the amount of alkyl ketene dimer added is too high, such as 2.0 g in Comparative Example 8, although the Cobb value further decreases to 18.2 g / m³, it still fails to meet the water-blocking requirements of wood pulp paper substrates. 2 However, excessive hydrophobic waxy substances create severe steric hindrance on the fiber surface, hindering the hemiacetal crosslinking reaction between the aldehyde groups of dialdehyde starch and the cellulose hydroxyl groups at high temperatures. This leads to the destruction of the crosslinking network, macroscopically manifested as a sharp drop in wet tensile strength retention to 26.4% and a significant deterioration in folding endurance to 105 cycles. This invention strictly limits the amount of alkyl ketene dimer to 0.5-1.5 parts (Examples 1, 6, 7), balancing the microscopic interfacial competition between "sizing water resistance" and "hemietal crosslinking," achieving the optimal combined effect of water resistance and mechanical strength.

[0165] Comparing the test data of Example 1 and Comparative Example 6, it can be seen that, under the premise that the retention rate and mechanical properties of the dialdehyde starch are basically the same, the Cobb value of Example 1 is 22.5 g / m³. 2 It exhibits excellent water-blocking performance; while the Cobb value of Comparative Example 6 increased significantly to 39.4 g / m³. 2The water-blocking performance deteriorated significantly. This data difference intuitively and powerfully demonstrates the "co-precipitation trapping effect" caused by the specific feeding sequence of the present invention: In Example 1, the alkyl ketene dimer dispersed first was trapped in situ by the microgel that subsequently underwent phase change precipitation, greatly improving the retention rate of the sizing agent; while in Comparative Example 6, the microgel precipitated first, and the subsequently added alkyl ketene dimer missed the three-dimensional trapping process at the moment of phase change, resulting in a large amount of sizing agent being released and lost with the white water; this comparative experiment conclusively confirms that there is a significant synergistic effect between the microgel phase change mechanism and the alkyl ketene dimer in the present invention.

[0166] As shown in Table 1, the biodegradability test results indicate that the paper-plastic composite packaging materials prepared after completing step S4 in Examples 1 to 7 have a biodegradability rate of 90.9%-92.6% at 180 days, which shows that the paper-plastic composite packaging materials composed of wood pulp paper base layer and polyvinyl alcohol / thermoplastic starch biodegradable plastic layer have good biodegradability.

[0167] The paper-plastic composite packaging materials prepared in Comparative Examples 1 to 8 showed biodegradability rates of 89.8%–93.4% at 180 days. All groups used the same biodegradable plastic layer, therefore the overall difference in biodegradability rates between groups was small. This indicates that the different wood pulp paper base layer preparation conditions used in this study did not significantly affect the biodegradability of the final paper-plastic composite packaging materials. Comparative Example 8 had a higher amount of alkyl ketene dimer added, resulting in a relatively lower 180-day biodegradability rate; Comparative Example 7 had a lower amount of alkyl ketene dimer added, resulting in a relatively higher 180-day biodegradability rate.

[0168] The above results demonstrate that after forming a polyvinyl alcohol and thermoplastic starch biodegradable plastic layer on the surface of the wood pulp paper base layer, the resulting paper-plastic composite packaging material can maintain a high final aerobic biodegradation capacity, thereby giving the paper-plastic composite packaging material of the present invention good environmental treatment adaptability.

[0169] In summary, the biodegradable paper-plastic composite packaging material and its preparation method of the present invention combine the acidic pre-preparation of microgel suspension with a neutral pulp mixing environment to prepare a wood pulp paper base layer with good wet strength, folding endurance and surface water resistance; furthermore, a biodegradable plastic layer is formed on at least one side of the surface of the wood pulp paper base layer, so that the resulting material has both the mechanical support of the wood pulp paper base layer and the surface protection of the biodegradable plastic layer, providing a technical approach for the preparation of green paper-plastic composite packaging materials.

[0170] Based on the preferred embodiments of the present invention described above, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a biodegradable paper-plastic composite packaging material, characterized in that, Includes the following steps: S1. Chitosan-coupled modified lignocellulose nanofibers and dialdehyde starch are mixed in water, the pH of the system is adjusted to 3.5-4.5, and the mixture is stirred at 40-50℃ for 30-45 min to obtain a microgel suspension. The molar ratio of the aldehyde group in the dialdehyde starch to the amino group in the chitosan-coupled modified lignocellulose nanofiber is 5:1-8:

1. S2. Adjust the pH value of the basic wood pulp suspension to 7.0-7.5, and then add the alkyl ketene dimer and the microgel suspension obtained in step S1 to the basic wood pulp suspension, and mix them evenly to obtain paper pulp. S3. The paper pulp obtained in step S2 is wire-fed, formed, and pressed to obtain a wet paper sheet; the wet paper sheet is subjected to multi-stage drying, wherein when the moisture content of the wet paper sheet drops to 30%-40%, the drying temperature is controlled at 85-95℃ and maintained for 1-2 minutes; then the temperature is raised to 110-115℃ and cured for 30-60 seconds to obtain the wood pulp paper base layer; S4. A biodegradable plastic coating liquid containing polyvinyl alcohol, thermoplastic starch and glycerin is coated on at least one side of the wood pulp paper base layer, and then dried and hot-pressed to form a biodegradable plastic layer, thereby obtaining the biodegradable paper-plastic composite packaging material.

2. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S1, the degree of oxidation of the dialdehyde starch is 40%-60%.

3. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S1, the chitosan-coupled modified lignocellulose nanofibers are prepared through the following steps: A suspension of lignocellulose nanofibers with carboxyl groups on the surface was mixed with a crosslinking agent for activation treatment. Then, a chitosan solution with a degree of deacetylation ≥95% was added. The mixture was stirred at a constant temperature under conditions of pH 5.0-5.5 and temperature 45-50℃. After the reaction was completed, the nanofibers were washed to obtain the final product. The crosslinking agent is a mixture of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide.

4. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S2, the basic wood pulp suspension contains calcium carbonate filler; The specific steps of adding the alkyl ketene dimer and the microgel suspension prepared in step S1 are as follows: First, the alkyl ketene dimer is added to the base wood pulp suspension. Then, the microgel suspension is added dropwise or sprayed into the base wood pulp suspension at a stirring speed of 800-1200 rpm.

5. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S2, the base wood pulp in the base wood pulp suspension is composed of 40-60 parts of long fiber softwood pulp and 40-60 parts of short fiber hardwood pulp, based on the weight of the oven-dry pulp. The long-fiber softwood pulp has a freeness of 38-42°SR, and the short-fiber hardwood pulp has a freeness of 28-32°SR.

6. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S2, after adding the microgel suspension, cationic polyacrylamide is also added to the base wood pulp suspension; The amount of cationic polyacrylamide added is 0.02%-0.05% based on the weight of the oven-dry slurry.

7. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S3, the pressing is a multi-stage roller pressing, and the moisture content of the wet paper sheet after being pressed by the multi-stage roller is 50%-55%.

8. The method for preparing a biodegradable paper-plastic composite packaging material according to claim 1, characterized in that, In step S3, the multi-stage drying is carried out in a multi-cylinder paper machine; The drying temperature of 85-95℃ is controlled in the front drying cylinder of the multi-cylinder paper machine, and the temperature is raised to 110-115℃ in the rear drying cylinder of the multi-cylinder paper machine. The final moisture content of the cured wood pulp paper base layer is 6%-8%.

9. A pulp composition for the wood pulp paper base layer of a biodegradable paper-plastic composite packaging material, characterized in that, Including basic wood pulp suspensions, alkyl ketene dimers, and microgel suspensions; The microgel suspension was prepared by mixing chitosan-coupled modified lignocellulose nanofibers with dialdehyde starch in water, adjusting the pH of the system to 3.5-4.5, and stirring the mixture at 40-50℃ for 30-45 minutes. The molar ratio of the aldehyde group in the dialdehyde starch to the amino group in the chitosan-coupled modified lignocellulose nanofiber is 5:1-8:

1. The overall pH value of the slurry composition is 7.0-7.5; Based on the weight parts of oven-dried pulp, the base wood pulp in the base wood pulp suspension is 100 parts, the microgel suspension is 3-8 parts by oven-dried mass, and the alkyl ketene dimer is 0.5-1.5 parts.

10. A biodegradable paper-plastic composite packaging material, characterized in that, The biodegradable paper-plastic composite packaging material is prepared by the preparation method according to any one of claims 1 to 8; the biodegradable paper-plastic composite packaging material includes a wood pulp paper base layer and a biodegradable plastic layer disposed on at least one side surface of the wood pulp paper base layer.